On the error of the interpolation by bilinear splines - Shabozov, M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the problem of approximation of functions from the classes Wr,s H ω and Wr,s H ω,2by bilinear splines. For some values of r ands, we obtain exact estimates of the error.